Bioaccumulation and partitioning of PFAS in an AFFF-impacted freshwater system: Invasive Asian clams as indicators of surface water contamination - Katharina Pankratz; Anna Gotsiridze; Robin Taylor Wilson; Nathaniel R. Warner (Environmental Pollution, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Gold nanoparticles loaded filter paper: A recyclable nanozyme for colorimetric determination of Hg2+ in tap water and beef - Melisew Tadele Alula; Peter Lemmens; Nicolette R. Hendricks-Leukes; Tiny Motalaote; Markus Etzkorn; Lindsay Robin Wilson; Felicity Babuseng (Food Control, 2025)

Reproductive biology of invasive grass carp ( Ctenopharyngodon idella ) in two North American systems - Tammy M. Wilson; Matthew R. Acre; Fred Williams; Robin D. Calfee; Christine M. Mayer; Robert L. Mapes; Chris M. Kemp; Ryan T. Young; Michael E. Byrne (Journal of Fish Biology, 2025)
Grass carp ( Ctenopharyngodon idella ) are nonnative, herbivorous freshwater fish that represent an ecological threat in North American waters. However, data are limited on reproductive biology specific to wild populations in midwestern North America, despite recent concern for grass carp establishment within the Great Lakes. Basic information on reproductive traits could be useful to determine reproductive potential, inform future population modelling and provide information to aid control efforts. Our objectives were to evaluate grass carp age‐at‐maturity, spawning season timing, fecundity type, developmental timing and spawning strategy. Additionally, we evaluated the reliability of the gonadosomatic index (GSI) as a proxy for identifying mature grass carp and compared body condition across study areas. We sampled grass carp in portions of the Mississippi River watershed within the state of Missouri and within the Lake Erie basin. Based on gonad histological samples ( n = 274), grass carp are batch spawners with indeterminate fecundity and asynchronous ovarian developmental timing. This allows flexibility in their spawning, exemplified by a protracted spawning season in Lake Erie (April to November) in temperatures ranging from 12.3 to 27.3°C. Minimum observed age‐at‐maturity for females in Missouri and for both males and females in the Lake Erie population was age‐3 and age‐2 for males in Missouri. Accuracy of GSI as a measure of maturity during the spawning season was 89.7% and 87.5%, for females and males, respectively. Compared to Missouri, grass carp in Lake Erie had a significantly higher body condition, and females ready to spawn had significantly higher GSI values, suggesting that the grass carp in Lake Erie are healthier and more fecund relative to Missouri and, if left uncontrolled, potentially have a high probability of establishment within the Great Lakes. The results of this study will allow managers to identify the reproductive status of grass carp in the field and more accurately estimate populations and reproductive potential.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The effects of rain and drought on incidence of enteric disease in Pennsylvania (2010–2019) - Miriam Wamsley; Robin Taylor Wilson; Heather M. Murphy (Environmental Research, 2025)

Seasonal drought treatments impact plant and microbial uptake of nitrogen in a mixed shrub grassland on the Colorado Plateau - Rebecca Finger‐Higgens; David L. Hoover; Anna C. Knight; Savannah L. Wilson; Tara B. B. Bishop; Robin Reibold; Sasha C. Reed; Michael C. Duniway (Ecology, 2024)
For many drylands, both long‐ and short‐term drought conditions can accentuate landscape heterogeneity at both temporal (e.g., role of seasonal patterns) and spatial (e.g., patchy plant cover) scales. Furthermore, short‐term drought conditions occurring over one season can exacerbate long‐term, multidecadal droughts or aridification, by limiting soil water recharge, decreasing plant growth, and altering biogeochemical cycles. Here, we examine how experimentally altered seasonal precipitation regimes in a mixed shrub grassland on the Colorado Plateau impact soil moisture, vegetation, and carbon and nitrogen cycling. The experiment was conducted from 2015 to 2019, during a regional multidecadal drought event, and consisted of three precipitation treatments, which were implemented with removable drought shelters intercepting ~66% of incoming precipitation including: control (ambient precipitation conditions, no shelter), warm season drought (sheltered April–October), and cool season drought (sheltered November–March). To track changes in vegetation, we measured biomass of the dominant shrub, Ephedra viridis , and estimated perennial plant and ground cover in the spring and the fall. Soil moisture dynamics suggested that warm season experimental drought had longer and more consistent drought legacy effects (occurring two out of the four drought cycles) than either cool season drought or ambient conditions, even during the driest years. We also found that E. viridis biomass remained consistent across treatments, while bunchgrass cover declined by 25% by 2019 across all treatments, with the earliest declines noticeable in the warm season drought plots. Extractable dissolved inorganic nitrogen and microbial biomass nitrogen concentrations appeared sensitive to seasonal drought conditions, with dissolved inorganic nitrogen increasing and microbial biomass nitrogen decreasing with reduced soil volumetric water content. Carbon stocks were not sensitive to drought but were greater under E. viridis patches. Additionally, we found that under E. viridis , there was a negative relationship between dissolved inorganic nitrogen and microbial biomass nitrogen, suggesting that drought‐induced increases in dissolved inorganic nitrogen may be due to declines in nitrogen uptake from microbes and plants alike. This work suggests that perennial grass plant–soil feedbacks are more vulnerable to both short‐term (seasonal) and long‐term (multiyear) drought events than shrubs, which can impact the future trajectory of dryland mixed shrub grassland ecosystems as drought frequency and intensity will likely continue to increase with ongoing climate change.

A newly discovered trematode parasite infecting the bay scallop, Argopecten irradians - Hailea F.H. Boggess; Robin L. Varney; D. Wilson Freshwater; Tal Ben-Horin; Carolina Preister; Hannah McCurry; Ami E. Wilbur; Julia C. Buck (Aquaculture, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Childhood Cancer Information-Seeking: Findings from the National Cancer Institute’s Cancer Information Service - Robin C. Vanderpool; Grace Huang; Ashley Wilson; Rebecca Gordon; Michelle A. Mollica; Candace Deaton Maynard (Journal of Cancer Education, 2023)

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Patient Engagement: an Assessment of Canadian Radiotherapy Programs’ Current Practices, Perceived Barriers, and Facilitators - Gabrielle Robin; Erika Brown; Carol-Anne Davis; Louise Bird; Lianne Wilson; Ross Halperin; Michael Brundage; Jennifer Croke; Cody Harper; Meredith Giuliani; Amanda Caissie (Journal of Cancer Education, 2022)

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Coffee intake and trace element blood concentrations in association with renal cell cancer among smokers - Hongke Wu; Stephanie Weinstein; Lee E. Moore; Demetrius Albanes; Robin Taylor Wilson (Cancer Causes & Control, 2022)

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

Reflections on the scientific life and legacy of Professor Ted Milton (10 April 1954 – 8 June 2021) - Karen Anderson; Paul Aplin; Paul Curran; Jadunandan Dash; Angela Harris; Liz Rollin; John Shears; Geoff Smith; Robin Wilson (International Journal of Remote Sensing, 2021)

Aspartate or arginine? Validated redox state X-ray structures elucidate mechanistic subtleties of FeIV = O formation in bacterial dye-decolorizing peroxidases - Marina Lučić; Michael T. Wilson; Dimitri A. Svistunenko; Robin L. Owen; Michael A. Hough; Jonathan A. R. Worrall (JBIC Journal of Biological Inorganic Chemistry, 2021)
Structure determination of proteins and enzymes by X-ray crystallography remains the most widely used approach to complement functional and mechanistic studies. Capturing the structures of intact redox states in metalloenzymes is critical for assigning the chemistry carried out by the metal in the catalytic cycle. Unfortunately, X-rays interact with protein crystals to generate solvated photoelectrons that can reduce redox active metals and hence change the coordination geometry and the coupled protein structure. Approaches to mitigate such site-specific radiation damage continue to be developed, but nevertheless application of such approaches to metalloenzymes in combination with mechanistic studies are often overlooked. In this review, we summarize our recent structural and kinetic studies on a set of three heme peroxidases found in the bacterium Streptomyces lividans that each belong to the dye decolourizing peroxidase (DyP) superfamily. Kinetically, each of these DyPs has a distinct reactivity with hydrogen peroxide. Through a combination of low dose synchrotron X-ray crystallography and zero dose serial femtosecond X-ray crystallography using an X-ray free electron laser (XFEL), high-resolution structures with unambiguous redox state assignment of the ferric and ferryl (Fe IV = O) heme species have been obtained. Experiments using stopped-flow kinetics, solvent-isotope exchange and site-directed mutagenesis with this set of redox state validated DyP structures have provided the first comprehensive kinetic and structural framework for how DyPs can modulate their distal heme pocket Asp/Arg dyad to use either the Asp or the Arg to facilitate proton transfer and rate enhancement of peroxide heterolysis. Graphic abstract

Disrupted parahippocampal and midbrain function underlie slower verbal learning in adolescent-onset regular cannabis use - Grace Blest-Hopley; Aisling O’Neill; Robin Wilson; Vincent Giampietro; Sagnik Bhattacharyya (Psychopharmacology, 2021)
Rationale Prolonged use of cannabis, the most widely used illicit drug worldwide, has been consistently associated with impairment in memory and verbal learning. Although the neurophysiological underpinnings of these impairments have been investigated previously using functional magnetic resonance imaging (fMRI), while performing memory tasks, the results of these studies have been inconsistent and no clear picture has emerged yet. Furthermore, no previous studies have investigated trial-by-trial learning. Objectives We aimed to investigate the neural underpinnings of impaired verbal learning in cannabis users as estimated over repeated learning trials. Methods We studied 21 adolescent-onset regular cannabis users and 21 non-users using fMRI performed at least 12 h after last cannabis use, while they performed a paired associate verbal learning task that allowed us to examine trial-by-trial learning. Brain activation during repeated verbal encoding and recall conditions of the task was indexed using the blood oxygen level-dependent haemodynamic response fMRI signal. Results There was a significant improvement in recall score over repeated trials indicating learning occurring across the two groups of participants. However, learning was significantly slower in cannabis users compared to non-users ( p = 0.032, partial eta-squared = 0.108). While learning verbal stimuli over repeated encoding blocks, non-users displayed progressive increase in recruitment of the midbrain, parahippocampal gyrus and thalamus ( p = 0.00939, partial eta-squared = 0.180). In contrast, cannabis users displayed a greater but disrupted activation pattern in these regions, which showed a stronger correlation with new word-pairs learnt over the same blocks in cannabis users than in non-users. Conclusions These results suggest that disrupted medial temporal and midbrain function underlie slower learning in adolescent-onset cannabis users.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Age, geological setting, and paragenesis of heavy rare earth element mineralization of the Tanami region, Western Australia - Teimoor Nazari-Dehkordi; Carl Spandler; Nicholas H. S. Oliver; Robin Wilson (Mineralium Deposita, 2020)

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Loggerhead Turtles (Caretta caretta) in the California Current: Abundance, Distribution, and Anomalous Warming of the North Pacific - Tomoharu Eguchi; Sam McClatchie; Cara Wilson; Scott R. Benson; Robin A. LeRoux; Jeffrey A. Seminoff (Frontiers in Marine Science, 2018)

Correction to: The Neural Substrate of Reward Anticipation in Health: A Meta-Analysis of fMRI Findings in the Monetary Incentive Delay Task - Robin Paul Wilson; Marco Colizzi; Matthijs Geert Bossong; Paul Allen; Matthew Kempton; Sagnik Bhattacharyya (Neuropsychology Review, 2018)

The Neural Substrate of Reward Anticipation in Health: A Meta-Analysis of fMRI Findings in the Monetary Incentive Delay Task - Robin Paul Wilson; Marco Colizzi; Matthijs Geert Bossong; Paul Allen; Matthew Kempton; Sagnik Bhattacharyya (Neuropsychology Review, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

A conceptual snapsot of a big coastal dune aquifer: Magilligan, Northern Ireland - N. S. Robins; P. Wilson (Journal of Coastal Conservation, 2017)

Metal-contaminated potato crops and potential human health risk in Bolivian mining highlands - Alan E. Garrido; William H. J. Strosnider; Robin Taylor Wilson; Janette Condori; Robert W. Nairn (Environmental Geochemistry and Health, 2017)

When is a forest a forest? Forest concepts and definitions in the era of forest and landscape restoration - Robin L. Chazdon; Pedro H. S. Brancalion; Lars Laestadius; Aoife Bennett-Curry; Kathleen Buckingham; Chetan Kumar; Julian Moll-Rocek; Ima Célia Guimarães Vieira; Sarah Jane Wilson (Ambio, 2016)

Invertebrate diversity of the unexplored marine western margin of Australia: taxonomy and implications for global biodiversity - Gary C. B. Poore; Lynda Avery; Magda Błażewicz-Paszkowycz; Joanna Browne; Niel L. Bruce; Sarah Gerken; Chris Glasby; Elizabeth Greaves; Anna W. McCallum; David Staples; Anna Syme; Joanne Taylor; et al. (Marine Biodiversity, 2015)

Productivity enhances benthic species richness along an oligotrophic I ndian O cean continental margin - Anna W. McCallum; Skipton Woolley; Magda Błażewicz‐Paszkowycz; Joanna Browne; Sarah Gerken; Rudy Kloser; Gary C. B. Poore; David Staples; Anna Syme; Joanne Taylor; Genefor Walker‐Smith; Alan Williams; et al. (Global Ecology and Biogeography, 2015)
Aims Marine soft sediments cover much of the deep ocean and are one of the largest habitats in the world, yet much of our understanding about their diversity is based on sampling in the N orth A tlantic. The deep‐sea benthos provides a simplified environment in which to explore the processes which maintain species richness. Here we investigate the influence of energy and habitat complexity on benthic species richness along an oligotrophic continental margin within the I ndian O cean. Location The upper continental margin of western A ustralia ( c . 13–35° S , 100–1000 m depth). Methods We examined the species richness of selected polychaetes ( A nnelida) and crustaceans in sediment grab samples. We used generalized linear models and hierarchical partitioning to examine the relationship and relative importance of temperature, productivity (particulate organic carbon flux, net primary productivity and depth) and habitat complexity (sediment particle size diversity and grain size) on species richness at 51 sites. Results In contrast to benthic studies in the N orth A tlantic, we found that species richness was higher on the shelf than on the slope. Species richness was positively correlated with net primary productivity; this relationship was influenced by high species richness in two areas where oceanic mixing is known to enhance primary productivity. Habitat heterogeneity and temperature were less influential. Main conclusion This study represents one of the first extensive quantitative studies of deep‐water benthos in the I ndo‐ W est P acific, and provides further evidence that bathymetric gradients of species richness are variable between regions, probably due to variation in local oceanography and productivity regimes. Our findings provide support for the overriding influence of productivity on species richness, even over relatively small ranges in depth and productivity. As climate change is expected to modify biogeochemical fluxes to the deep seafloor, this is likely to affect the communities of deep‐sea fauna.

Nanomaterial risk screening: a structured approach to aid decision making under uncertainty - Christian E. H. Beaudrie; Milind Kandlikar; Robin Gregory; Graham Long; Tim Wilson (Environment Systems and Decisions, 2015)

A fundamental dispute: A discussion of “On some fundamentals of igneous petrology” by Bruce D. Marsh, Contributions to Mineralogy and Petrology (2013) 166: 665–690 - Rais Latypov; Tony Morse; Brian Robins; Richard Wilson; Grant Cawthorn; Christian Tegner; Marian Holness; Charles Lesher; Steve Barnes; Brian O’Driscoll; Ilya Veksler; Michael Higgins; et al. (Contributions to Mineralogy and Petrology, 2015)

The floral transition is not the developmental switch that confers competence for the Arabidopsis age-related resistance response to Pseudomonas syringae pv. tomato - Daniel C. Wilson; Philip Carella; Marisa Isaacs; Robin K. Cameron (Plant Molecular Biology, 2013)

Advanced remote sensing: terrestrial information extraction and applications , by Shunlin Liang, Xiaowen Li and Jindi Wang - Robin Wilson (International Journal of Remote Sensing, 2013)

Transformation of the oilseed crop Camelina sativa by Agrobacterium-mediated floral dip and simple large-scale screening of transformants - Xunjia Liu; Jennifer Brost; Carolyn Hutcheon; Robin Guilfoil; Anna K. Wilson; Sharon Leung; Christine K. Shewmaker; Suzanne Rooke; Thu Nguyen; Jack Kiser; Jay De Rocher (In Vitro Cellular & Developmental Biology - Plant, 2012)

Variation for tolerance to high concentration of ferrous iron (Fe2+) in Australian hexaploid wheat - Hossein Khabaz-Saberi; Zed Rengel; Robin Wilson; Timothy L. Setter (Euphytica, 2010)

Equivalent effects of acute tryptophan depletion on REM sleep in ecstasy users and controls - Robin L. Carhart-Harris; David J. Nutt; Marcus R. Munafo; David M. Christmas; Sue J. Wilson (Psychopharmacology, 2009)

Comparison of genetic and cytogenetic maps of hexaploid wheat (Triticum aestivum L.) using SSR and DArT markers - Michael G. Francki; Esther Walker; Allison C. Crawford; Sue Broughton; Herbert W. Ohm; Iain Barclay; Robin E. Wilson; Robyn McLean (Molecular Genetics and Genomics, 2009)

A novel family of diversified immunoregulatory receptors in teleosts is homologous to both mammalian Fc receptors and molecules encoded within the leukocyte receptor complex - James L. Stafford; Eva Bengtén; Louis Du Pasquier; Robin D. McIntosh; Sylvie M. Quiniou; L. W. Clem; Norman W. Miller; Melanie Wilson (Immunogenetics, 2006)

Phylogeny of nereidids (Polychaeta, Nereididae) with paragnaths - Torkild Bakken; Robin S. Wilson (Zoologica Scripta, 2005)
A phylogenetic analysis was conducted of the Nereidinae — those members of the Nereididae (Polychaeta) with pharyngeal paragnaths. We had two objectives: to test the monophyly of currently accepted genera, subgenera and informal subgeneric groupings within the Nereidinae, and, if warranted, to propose a more natural classification of the Nereidinae. Parsimony analyses were undertaken, including 52 terminal taxa from all genera and informal groupings from the large heterogeneous genera Nereis , Ceratonereis , Neanthes and Perinereis . Analyses of a character set of 52 informative characters yielded more than 10 000 equally parsimonious trees with a length of 176 steps (consistency index [CI] = 0.34, retention index [RI] = 0.66). Reweighting three times resulted in 445 most parsimonious trees with length 54.62 (CI = 0.59, RI = 0.79). Many characters widely used in nereidid systematics were found to exhibit high levels of homoplasy. The most parsimonious trees could not be rooted such that the selected ingroup, ‘Nereididae with paragnaths’, was monophyletic, causing us to reject the monophyly of the Nereidinae as currently defined. The following genera were well supported by the parsimony analyses and are newly diagnosed: Alitta , Ceratonereis , Pseudonereis , Simplisetia , Solomononereis and Unanereis . Alitta succinea , Pseudonereis cortezi , Pseudonereis noodti and Pseudonereis pseudonoodti are proposed as new combinations. The parsimony analysis supported the monophyly of neither Composetia , Neanthes , Nereis and Perinereis nor of any new groupings of remaining species presently placed in those genera. It is these poorly supported genera that comprise most species of Nereididae.

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Effect of Medium Composition on the Susceptibility of Oral Streptococci to Mercuric Chloride - Rachel Pike; Paul Stapleton; Victoria Lucas; Graham Roberts; Robin Rowbury; Hillary Richards; Peter Mullany; Michael Wilson (Current Microbiology, 2002)

Resistance to septoria nodorum blotch in the Aegilops tauschii accession RL5271 is controlled by a single gene - Noel E.A. Murphy; Robert Loughman; Robin Wilson; Evans S. Lagudah; Rudi Appels; Michael G.K. Jones (Euphytica, 2000)

Stool Water Content and Colonic Drug Absorption: Contrasting Effects of Lactulose and Codeine - John M. Hebden; Peter J. Gilchrist; Alan C. Perkins; Clive G. Wilson; Robin C. Spiller (Pharmaceutical Research, 1999)

Regional Differences in Quinine Absorption from the Undisturbed Human Colon Assessed Using a Timed Release Delivery System - John M. Hebden; Clive G. Wilson; Robin C. Spiller; Peter J. Gilchrist; Elaine Blackshaw; Malcolm E. Frier; Alan C. Perkins (Pharmaceutical Research, 1999)

Discrete consumers, small scale resource heterogeneity, and population stability - Roger M. Nisbet; Andre M. De Roos; William G. Wilson; Robin E. Snyder (Ecology Letters, 1998)
We present a consumer‐resource model in which individual consumers subsist on a continuum of resource distributed over a very large number of small “bite‐sized” patches, each patch being sufficiently small that all its resource is eaten whenever a consumer visits. This form of consumer–resource interaction forces a heterogeneous distribution of resource among the patches, and may dampen out the large amplitude, consumer‐resource cycles that are predicted by traditional models of well‐mixed, spatially homogeneous systems. The resource equilibrium does not increase with enrichment, a prediction that distinguishes this model from models that invoke direct or indirect consumer density dependence as a stabilizing mechanism.

Effects of Land‐Use and Tsetse Fly Control on Bird Species Richness in Southwestern Ethiopia - Cathleen J. Wilson; Robin S. Reid; Nancy L. Stanton; Brian D. Perry (Conservation Biology, 1997)
Successful control of tsetse (Glossina spp.)‐transmitted trypanosomiasis in the Ghibe Valley, Ethiopia, appears to have accelerated conversion of wooded grassland into cropland. Land conversion, in turn, may have fragmented wildlife habitat. Our objective was to assess the influence of the expansion of agricultural land‐use, brought about by tsetse control, on ecological properties by using bird species richness and composition as indicators of environmental impacts. We sampled bird species richness and composition (using Timed‐Species counts) and habitat structure (using field sampling and remote sensing) in four land cover/land‐use types in areas subjected to tsetse fly control and adjacent areas without control. At the height of the growing season bird species numbers and vegetative complexity were greater in the small‐holder, oxen‐plowed fields and riparian woodlands than in wooded grasslands or in large‐holder, tractor‐plowed fields. Species composition was highly dissimilar (40–70% dissimilarity) comparing among land‐use types, with many species found only in a single type. This implies that trypanosomiasis control that results in land conversion from wooded grasslands to small‐holder farming in this region may have no adverse impacts on bird species numbers but will alter composition. These results also suggest that moderate land‐use by humans (e.g., small‐holder field mosaics) increases habitat heterogeneity and bird species richness relative to high levels of use (e.g., tractor‐plowed fields). Tsetse control may be indirectly maintaining species richness in the valley by encouraging the differential spread of these small‐scale, heterogeneous farms in place of large‐scale, homogeneous farms. Nevertheless, if the extent of small‐holder farms significantly exceeds that of present levels, negative impacts on bird species richness and large shifts in species composition may occur.